2010
DOI: 10.1007/bf03195722
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining carrot (Daucus carota L.) plants in isolated microspore cultures

Abstract: Microspores were cultured on the modified B5 liquid medium containing 2.4D (0.1 mg L(-1)), NAA (0.1 mg L(-1)), L-glutamine (500 mg L(-1), L-serine (100 mg L(-1)), and sucrose (100 g L(-1)). The developmental stages of microspores and divisions were observed. Initially, the formation of binuclear and multicellular structures was noticed. Plants regenerated in the cultures in which the tetrad stage of microsporogenesis had predominated. Embryoids were still forming 24 weeks after the cultures were set up. Six we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 15 publications
(12 reference statements)
3
19
0
Order By: Relevance
“…The shortest time span was required by 900Q1 with only 38 days. This variation in rate of development was similar to findings by Górecka et al (2010), and much longer than those observed in Brassica species (Fang et al 2006;Zhang et al 2008;Bhowmik et al 2011;Takahira et al 2011). The ten different genotype accessions were selected for testing over different years (Table 2).…”
Section: Influence Of Genotypesupporting
confidence: 80%
See 4 more Smart Citations
“…The shortest time span was required by 900Q1 with only 38 days. This variation in rate of development was similar to findings by Górecka et al (2010), and much longer than those observed in Brassica species (Fang et al 2006;Zhang et al 2008;Bhowmik et al 2011;Takahira et al 2011). The ten different genotype accessions were selected for testing over different years (Table 2).…”
Section: Influence Of Genotypesupporting
confidence: 80%
“…Agronomic characters measured included leaf color intensity, leaf size, leaf dissection, and petiole color of haploid, DH and triploid plantlets. Górecka et al (2010) noticed the first divisions of carrot immature microspores under a microscope about 2 weeks after culture initiation, while these structures could be observed with the naked eye after 3 weeks to 6 months. In our study, small embryos or calli were visible with the naked eye about 5 weeks after the IMC was established (Fig.…”
Section: Ploidy Identification and Morphological Characters Of Regenementioning
confidence: 99%
See 3 more Smart Citations